Thermal and noise insulation performance interaction of building envelope during building simulation optimization in tropical climates. (August 2021) - Khan, Nabeel Ahmed; Bhattacharjee, Bishwajit
Abstract: Building simulation optimization is being increasingly adopted by researchers and designers as an efficient methodology for early-stage design and selection of building envelope parameters. Thermal performance has been the focus of many of the proposed methodologies owing to large energy consumption in buildings to maintain thermal comfort for the occupants. While the envelope is optimized to enhance its thermal performance, the effect on its noise insulation performance is not paid any attention as both performance objectives are assumed to be non-interacting or non-conflicting. It may be possible that the optimization for thermal performance may lead to degradation in noise insulation performance or vice versa. The present work aims to study the interaction between the thermal and noise insulation performance of the building envelope during a building simulation optimization process when both the performance objectives are optimized independently and simultaneously. The results obtained show the adverse effect of independent thermal and noise insulation optimization on noise insulation and thermal performance of the building envelope walls respectively. An exception was observed in the case of independent noise insulation optimization of both 8-hour and 24-hour conditioned buildings where average thermal performance of the final population was enhanced along with the noise insulation performance. Highlights: Effect of individual envelope thermal optimization on noise performance. Effect of individual envelope noise insulation optimization on thermal performance. Interaction of thermal-noise performance and advantages of combined optimization. Change in thermal-noise performance interaction with climate and occupancy types.